The Impact of Environmental Health Services in Primary Health Care on Improving the Behavior of Pulmonary Tuberculosis Patients in Banyuwangi Regency - Sheilla Mufidha Wahyuningtyas; Endang Sri Lestari; Jojok Mukono; Endro Sukmono (Universitas Airlangga, 2020)
Introduction: Tuberculosis (TB) is a global health crisis. Environmental health services in Primary health care provide counseling services, inspections and environmental health interventions. Research aims to determine the impact of environmental health services in Primary health care on the behavior of TB patients that includes the knowledge, attitudes and actions of pulmonary tuberculosis patients in the prevention of the transmission of pulmonary tuberculosis disease. Method: The method in this study was experimental quasi. Respondents were a new case of pulmonary TB at 6 Primary health care in Banyuwangi Regency April S/d June 2019. Pre test before obtaining environmental health services. Post test was given after counseling, inspection and environmental health intervention. Result and Discussion: The results showed a total of 24 respondents to the majority pulmonary tuberculosis patient was male (54.17%). Pre test knowledge of pulmonary TB patient is good (4.16%), enough (8.33%) and less (87.50%). Category Post test knowledge of TB patients acquired good (20.83%), sufficient category (75.00%) and less (4.20%). The average Pre test knowledge score is 37.70 and the Post test is 67.20. Category Prettest Action patients TB is good (4.16%) and less (95.83%). Category Post Test action patients pulmonary TB is good (54.17%), enough (41.67%) and less (4.16%) Which is an improvement in the form of masks, hand washing soap, the habit of spitting, the use of individual cutlery and drinking equipment, washing dinnerware and drinking with hot water/drying, drying the sleeping tools, opening a window every day, separate sleeping habits. Conclusion: The conclusion of this research is environmental health services in Primary health care in patients with pulmonary tuberculosis improves the behavior of TB patients in the form of increased knowledge, attitudes and actions of the patient in the prevention of disease transmission of TB.